2019
DOI: 10.1002/slct.201901070
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonic Acid Functionalized MIL‐101(Cr) Metal‐Organic Framework for Catalytic Production of Acetals

Abstract: A simple and green process for acetalization of benzaldehyde derivatives in the presence of a new solid acid nanocatalyst is reported. For this purpose, MIL-101(Cr) was synthesized in the absence of HF and then sulfonic acid functionalized MOF was prepared under mild conditions without using hazardous chemicals. First, the MIL-101(Cr) was functionalized with cysteamine as a non-toxic material to afford MIL-101(Cr)-SH. Then, reaction of the MIL-101(Cr)-SH with hydrogen peroxide as a clean oxidant followed by ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…Moreover, the new peak at 1044 cm −1 was indexed to the stretching mode of S−O in PS/ UiO-66(Zr), thus suggesting successful grafting of UiO-66(Zr) with −SO 3 − to give PS/UiO-66(Zr). 73 Similar results were also observed with UiO-67(Zr) and PS/UiO-67(Zr) (Figure S2).…”
Section: Resultssupporting
confidence: 83%
“…Moreover, the new peak at 1044 cm −1 was indexed to the stretching mode of S−O in PS/ UiO-66(Zr), thus suggesting successful grafting of UiO-66(Zr) with −SO 3 − to give PS/UiO-66(Zr). 73 Similar results were also observed with UiO-67(Zr) and PS/UiO-67(Zr) (Figure S2).…”
Section: Resultssupporting
confidence: 83%
“…The protonated carbonyl group undergoes the nucleophilic attack of O atom of the ethanol and subsequently, a second molecule of ethanol is added to the rhodium center (Step 3, Figure ). This last species releases the FDEA and a water molecule (Step 4, Figure ) that can thus star another catalytic cycle.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20] However, its acidity is highly dependent on coordinative unsaturated metal sites after removal of volatile molecules, which constrains flexible tunability of acidic strength and subsequent application scopes. [19,21] Thus, to overcome this drawback, some Brønsted acidic molecules or groups are introduced into MOFs via encapsulation [22][23][24] or post-modification. [25][26][27] In 2011, Kitagawa's group successfully functionalized MIL-101(Cr) with sulfonic groups (MIL-101(Cr)-SO 3 H) and found that sulfonic groups in the pores enormously improved the catalytic activity of MIL-101(Cr) for the cellulose hydrolysis reaction.…”
Section: S C H E M E 1 Bioactive Compounds Containing Tetrahydroquinoline Structural Fragmentsmentioning
confidence: 99%